2012
DOI: 10.1002/jcc.22940
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational averaging of the chemical shift in crystalline α‐glycine

Abstract: Averaging of the chemical shift over the molecular motion improves the simulated data and provides additional information about the temperature dependence and system dynamics. However, crystal modeling is difficult due to the limited precision of the plane-wave density functional theory (DFT) methods and approximate vibrational schemes. On the glycine example, we investigate how the averaging can be achieved within the periodic boundary conditions at the DFT level. The nuclear motion is modeled with the vibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 79 publications
(103 reference statements)
0
25
0
Order By: Relevance
“…It has been shown that dispersion correction did not significantly affect the calculated shieldings of solid glycine when the lattice parameters were fixed during geometry optimization in ref. 19 , in which the temperature dependence of the chemical shifts was studied. The center of mass was fixed to ensure that the random initial velocities did not result in translational motion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that dispersion correction did not significantly affect the calculated shieldings of solid glycine when the lattice parameters were fixed during geometry optimization in ref. 19 , in which the temperature dependence of the chemical shifts was studied. The center of mass was fixed to ensure that the random initial velocities did not result in translational motion.…”
Section: Methodsmentioning
confidence: 99%
“…[18][19] This method is computationally demanding and many approximations have to be adopted in practical computations, in particular for the treatment of the variation of the shielding with vibrational coordinates. However, the results confirmed an important vibrational contribution (up to almost 10 ppm for nitrogen atom) to isotropic chemical shifts, which was in qualitative agreement with the results of DFT-MD.…”
mentioning
confidence: 99%
“…It was shown previously that a dispersion correction did not affect the calculated magnetic shielding values of solid glycine significantly when the lattice parameters were fixed during geometry optimization. 63 The centre of mass in the simulation cell was fixed to ensure into 16 beads (which was found to be satisfactory in previous studies of molecular solids at 300 K [64][65] ) and total simulation time of 10 ps were used.…”
Section: Castep Calculationsmentioning
confidence: 99%
“…The accuracy of the force field used for the MD simulations was shown to be crucial for the results. By publishing more and more fitted reference shieldings, research groups in the field of NMR crystallography can collectively build up increasingly more accurate and independent estimates of a universal reference shielding, σ ref . This ab initio NMR crystallography approach, together with state‐of‐the‐art experimental NMR spectroscopy, will be valuable for the elucidation of the structural and dynamic properties of challenging solid‐state phases, even if no single crystals are available.…”
Section: Discussionmentioning
confidence: 99%
“…In reality, all molecular crystals undergo motion and lattice expansion due to the effect of temperature, and averaging over thermally occupied states is of significance to reduce the discrepancy between ss‐NMR theoretical calculations and experiments, even for non‐plastic phases. These phenomena have been studied in combination with, for example, vibrational averaging on a series of generated configurations at zero and finite temperatures, classical molecular dynamics (MD) simulations and ab initio MD simulations (including Born–Oppenheimer MD and path integral MD) …”
Section: Introductionmentioning
confidence: 99%